2006
DOI: 10.1007/s10646-006-0091-3
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological assessment of effluents in the Basque country (Northern Spain) by acute and chronic toxicity tests using Daphnia magna straus

Abstract: Acute pass/fail, multi-concentration tests, and 3-brood chronic toxicity tests with Daphnia magna Straus (Cladocera, Crustacea) were used to characterise industrial and municipal effluents from various sources. The effluents that "passed" the pass/fail tests had 48-h EC50 values >100% and reproduction No Observed Effect Concentration (NOECs) > or =100%, except for one effluent that had a reproduction NOEC of 31.6%. The acute multi-concentration toxicity tests allowed a rapid classification of effluents from Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
2
12
0
1
Order By: Relevance
“…This same effect, known by hormesis, was observed by Rodriguez et al [11], in Daphnia magna exposed to two metal surface coating effluents. These effluents contained metals like Ni, Zn, and Cr, and the researchers affirm that their presence may explain the reproduction effects.…”
Section: Discussionsupporting
confidence: 82%
“…This same effect, known by hormesis, was observed by Rodriguez et al [11], in Daphnia magna exposed to two metal surface coating effluents. These effluents contained metals like Ni, Zn, and Cr, and the researchers affirm that their presence may explain the reproduction effects.…”
Section: Discussionsupporting
confidence: 82%
“…Not surprisingly, D. magna proved to have good discrimination capacity in WET testing of a wide range of wastewater types, including metal-processing industry, even in cases when the effluent quality was in compliance with the regulations [22,26,40,41]. On the other hand, when only bacterial tests were applied in assessment of various environmental samples (not as a part of multitrophic battery of assays); the authors generally reported their good discrimination capacity [20,42].…”
Section: Applicability Of Bacterial Tests To Assessment Of Environmenmentioning
confidence: 98%
“…By using an in situ bioassessment approach, Maltby et al (2000) demonstrated receiving water toxicity and ecological degradation that were consistent with the results of WET tests performed on the point source discharge and concluded that systematic approach provides a comprehensive and ecologically relevant database for assessing the ecological risk posed by point source discharges, so that by applying a set of complementary diagnostic tools, resource managers and dischargers would gain greater confidence in the permit limits set for effluents and the methods used to monitor compliance. Quite a large number of specific research studies of ecotoxicity of industrial effluents using conventional toxicity tests combined with chemical quality assessment, were conducted world-wide, such as, for instance, in Portugal (Mendonca et al 2007), Spain (Rodriguez et al 2006), UK (Tinsley et al 2004), Italy (Guerra 2001), Netherlands (Tonkes et al 1999), Turkey (Sponza 2002), Lithuania and Estonia (Manusadzianas et al 2003), Argentina (Gomez et al 2001;Di Marzio et al 2005), Brasil (Araujo et al 2005) and South Korea (Ra et al 2006a). The conclusion from all the cited studies, which stands for our research as well, is that clear environmental benefit can be delivered by targeting the use of effluent bioassays at catchments with well defined water quality problems, where ecotoxicity from complex effluents is expected to be a contributing factor, despite compliance with chemical limits.…”
Section: Resultsmentioning
confidence: 99%
“…There are many unsolved problems and opened questions, such as: (a) the relationship between the results of WET and chemical-based effluent quality assessment (Rodriguez et al 2006;Mendonca et al 2007;Picado et al 2008;Boillot et al 2008;Ra et al 2008); (b) the contribution of individual toxicants to overall toxicity of the effluent (Sarakinos et al 2000); (c) the interaction between potentially present toxicants and other compounds in the effluent, and consequently, the bioavailability of toxicants (Cedergreen et al 2008;Ra et al 2006b;Kramer et al 2004); (d) the problem of toxicity identification evaluation in complex mixtures (Brack 2003;Gutiérrez et al 2008;CaffaroFilho et al 2008;Eunhee et al 2008); and (e) the increasing need to find, establish and standardise alternative methods and end-points, including the application of genomic based tools in WET approach, which would be more sensitive to priority pollutants and emerging substances (Barata et al 2008;Kwon et al 2008).…”
Section: Introductionmentioning
confidence: 99%